Controversies in ureteroscopy: lasers, scopes, ureteral access sheaths, practice patterns and beyond - Juliebø-Jones, Patrick; Keller, Etienne Xavier; De Coninck, Vincent; Uguzova, Sabine; Tzelves, Lazaros; Æsøy, Mathias Sørstrand; Beisland, Christian; Somani, Bhaskar K.; Ulvik, Øyvind (Frontiers in Surgery, 2023)
Ureteroscopy has become an increasingly popular surgical intervention for conditions such as urinary stone disease. As new technologies and techniques become available, debate regarding their proper use has risen. This includes the role of single use ureteroscopes, optimal laser for stone lithotripsy, basketing versus dusting, the impact of ureteral access sheath, the need for safety guidewire, fluoroscopy free URS, imaging and follow up practices are all areas which have generated a lot of debate. This review serves to evaluate each of these issues and provide a balanced conclusion to guide the clinician in their practice.